PENGARUH TINGKAT PENDIDIKAN PEMILIK, LAMA USAHA, DAN PELATIHAN AKUNTANSI TERHADAP PENGGUNAAN INFORMASI AKUNTANSI PADA UMKM DI KABUPATEN SUKOHARJO - Sudarsih Novi Amalia; Desy Nur Pratiwi; Yuwita Ariessa Pravasanti (JURNAL RUMPUN MANAJEMEN DAN EKONOMI, 2026)
This study aims to analyze the influence of the owner's education level, length of business, and accounting training on the use of accounting information by MSMEs in Sukoharjo Regency. This study employed a quantitative approach with multiple linear regression analysis, preceded by classical assumption testing. The data used in this study were primary data obtained directly through questionnaires distributed to MSMEs. The sample size was 100 respondents selected using specific techniques according to research criteria. The test tools used in this study included classical assumption tests (normality, multicollinearity, autocorrelation, and heteroscedasticity tests), as well as multiple linear regression tests consisting of t-tests, F-tests, and coefficient of determination (R²) tests. The results showed that simultaneously, the owner's education level, length of business, and accounting training significantly influenced the use of accounting information. The results of this study indicate that, partially, the owner's education level, length of business, and accounting training each had a positive and significant effect on the use of accounting information.